Of Cestodes and Men: Surgical Treatment of a Spinal Hydatid Cyst - Saul, Dominik; Seitz, Mark-Tilmann; Weiser, Lukas; Oberthür, Swantje; Roch, Jonathan; Bremmer, Felix; Perske, Christina; Viezens, Lennart; Sehmisch, Stephan; Lehmann, Wolfgang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The cestode Echinococcus granulosus causes hydatid disease. In addition to manifestations in the liver and lung, it can lead to cystic lesions in the spine.Case Description We report a 42-year-old male patient with primary hydatid disease in the eighth thoracic vertebra. The only clinical symptom was chronic back pain. Although laboratory findings were normal, imaging displayed lytic destruction that raised the suspicion of a metastatic disease. Diagnostics of the thoraces and abdomen did not reveal other pathologic abnormalities. Follow-up magnetic resonance imaging (MRI) depicted a progressive compression of the spinal cord and inhomogeneous structure in the fat-suppressed sequences. Because the Jamshidi biopsy was inconclusive, the tumor board recommended surgery. Dorsal decompression, spondylodesis of T6–T10, and vertebral column resection of T8 with complete cyst removal were performed. The resected vertebrae showed a mucous-like lesion with white granular tissue interfusing the whole vertebral body. A pathologic examination and enzyme-linked immunosorbent assay confirmed E. granulosus. Thus chemotherapy with albendazole was initiated. A follow-up MRI of the whole spine confirmed complete remission and found no additional resettlements. The patient's back pain was resolved without neurologic deficits.Conclusions For lytic manifestations of the vertebral column, hydatid cysts should be considered a differential diagnosis in addition to malignant metastasis, tuberculosis, and osteomyelitis. Thorough surgical resection and strict follow-up are necessary.
Keywords: echinococcus granulosus; hydatid cyst; hydatid disease; spinal osteolytic lesion